2017
DOI: 10.1016/j.amjsurg.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

The hypercoagulability paradox of chronic kidney disease: The role of fibrinogen

Abstract: Background Chronic kidney disease (CKD) patients have increased rates of bleeding as well as thrombosis. Fibrinogen and platelets combine to generate a mature clot, but in CKD platelets are dysfunctional. Therefore, we hypothesize that CKD patients have increased clot strength due to elevated fibrinogen levels. Methods Retrospective review of CKD patients (n=84) who had rTEG and fibrinogen levels measured. They were compared to healthy controls (n=134). Results CKD patients had statistically significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
1
23
1
6
Order By: Relevance
“…Whether PLN dogs have platelet hyper‐excitability or platelet dysfunction has not been evaluated previously. It is suspected, however, that this depends on many factors and is likely a dynamic process, similar to what is observed in human medicine . A recent study evaluating platelet function in healthy dogs and dogs with CKD using a different platelet function assay concluded that CKD dogs exhibited platelet dysfunction.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Whether PLN dogs have platelet hyper‐excitability or platelet dysfunction has not been evaluated previously. It is suspected, however, that this depends on many factors and is likely a dynamic process, similar to what is observed in human medicine . A recent study evaluating platelet function in healthy dogs and dogs with CKD using a different platelet function assay concluded that CKD dogs exhibited platelet dysfunction.…”
Section: Discussionmentioning
confidence: 89%
“…It is suspected, however, that this depends on many factors and is likely a dynamic process, similar to what is observed in human medicine. 41,42 A recent study evaluating platelet function in healthy dogs and dogs with CKD using a different platelet function assay concluded that CKD dogs exhibited platelet dysfunction. Some of the reported dogs had proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ESRD are prone to cardiovascular complications, and one of the contributing factors is the formation of thicker clots that are more resistant to fibrinolysis [ 5 , 6 ]. The focus of the current study was set on the fibrinogen structure-related changes in ESRD patients on PD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with chronic kidney disease (CKD) are at higher risk of cardiovascular morbidity and mortality [ 5 ]. Delayed clot formation, decreased lysis, and increased clot strength, as well as hypercoagulability found in patients with CKD, are to some extent mediated by fibrinogen [ 6 ]. This key component of the blood clotting process is a 340 kDa homodimer, consisting of two sets of three polypeptide chains (AαBβγ) 2 that are O- and/or N-glycosylated.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional laboratory tests of coagulation, TEG provides qualitative information throughout the entire “life-cycle” of a clot, from formation to lysis. 18 Several studies using TEG for patients undergoing hemodialysis access surgery have demonstrated that these patients are both hyper and hypocoaguable, with prolong clotting time but increased clot strength and impaired fibrinolysis 19 , 20 . Given that a properly functioning renal graft should correct uremia and produce greater amounts of urokinase relative to the patient’s native diseased kidneys, one would expect an improvement in fibrinolytic activity following transplantation with a good functioning graft.…”
Section: Introductionmentioning
confidence: 99%